The Problem of the Proper Name. The Cases of Jorge Barón Biza and Julián Herbert (2017)
Two texts about the pain of the other. Two convalescent mothers in hospital beds, two sons sitting in chairs next to their beds. Two sons writing in first person in order to escape the pain, with the simple difference that one of them uses his own name to do it and the other chooses to modify it. In this article I propose a parallel reading of Jorge Baron Biza ́s El desierto y su semilla [Desert Seeds] and Julián Herbert ́s Canción de tumba [Tomb Song], to examine the use of the proper name in both. In the analysis of the ambiguity between autobiography and novel, I ask questions about the use of the proper name in the two texts, in order, first of all, to establish the way in which the term “autofiction” operates; and secondly, to point, in each case, to the singularity of the narrative voice through this technique that creates tension between remembrance and memory